Caribbean public law - Fiadjoe, Albert (Cavendish Pub. LondonGB, 1996)
Focuses on the relationship between the courts and the executive branches of the government and on the role of judicial review in the constitutional and governmental framework of the English-speaking Commonwealth Caribbean.